Frequencies of polymorphisms in genes affecting the pharmacokinetics of warfarin in the Zaporizhzhia region - M. Yu. Kolesnik; Yа. М. Mykhailovskyi (Zaporožskij Medicinskij Žurnal)
The aim of the study: to establish the frequencies of polymorphisms in VKORC1, CYP2C9 and CYP4F2 genes among residents of the Zaporizhzhia region.